Implementasi Pendidikan Nilai Nasionalisme Dalam Pembelajaran Living Values - An-Nisa Apriani; Yusinta Dwi Ariyani (LITERASI (Jurnal Ilmu Pendidikan), 2017)
This research aims to investigate the implementation of educational values of nasionalism in the living values learning process on the preparation class at SD Tumbuh 1 Yogyakarta. The data were collected by qualitative-descriptive method. Participants of this research included the principal, the teachers, and the students. The object of this research is the process of living values learning. The data were collected by observation, interview, and documentation. The researcher used observation sheets and interview guides as the instruments of this research.  The data were analyzed by descriptive-analyzed technique and applied Miles and Huberman model. Many steps of data analysis were conducted, included measuring data reduction, displaying data, and conclusion. The validity of the data were checked by triangulation.The result showed that the implementation of educational values of nasionalism in the living values learning process involving the value of the award in diversity (tolerance), unity, and peace. Living values learning process includes three stages: planning, implementation, and evaluation. Learning plan of living values is based on signs EYCG curriculum (Years Earlier Curicullum guidence) and modified with multiple sources of reference. The learning plan includes syllabus and program description. The implementation of living values learning process emphasizes three elements of embeding moral values such as knowledge, feeling, and moral behavior. The evaluation of the living values learning process includes the assessment of learning outcome and learning process. Assessment of learning outcome has reached the domain of comprehension and moral behavior. Learning process assessment is conducted orally but rarely carried out by the teacher.